C Endothelial specific Nox2 over-expression increases susceptibility to angiotensin II induced aortic dissection. (16th May 2012) - Fan, L; Douglas, G; Bendall, J; McNeill, E; Channon, K
Abstract : Aortic dissection is a detrimental disease with high mortality. However, the mechanisms regulating the susceptibility to aortic dissection remain unknown. We hypothesise that endothelial oxidative stress due to the activation of the reactive oxygen species (ROS)-generating Nox2 enzyme play an important role in the development of aortic dissection. To investigate this, we generated transgenic mice (C57BL/6J background) with endothelial specific over-expression of Nox2 (Nox2-Tg) under the control of a tie-2 promoter. Expression of the human Nox2 transgene was confirmed by qRT-PCR to be found only in endothelial cells (EC) isolated from transgenic mice, and not in WT EC or vascular smooth muscle cells (VSMC) and macrophages isolated from either genotype. Wild-type (WT) littermates and Nox2-Tg male mice (6 months, n=11) were treated with vehicle or AngII (1 mg/kg/day) via subcutaneous mini-pump for 28 days. There was no significant difference in the pressor responses to AngII between WT and Nox2-Tg mice (WT 121±7 mm Hg vs Nox2-Tg 122±6 mm Hg). However, 5/11 Nox2-Tg mice developed aortic dissections compared to 0/11 WT mice after AngII infusion (p<0.001). Immunohistochemistry revealed significant increases in endothelial VCAM-1 expression, MMP activity and CD45+ inflammatory cell recruitment in the aortas of Nox2-Tg mice after 5 days of AngII infusion. Inflammatory cell recruitment was further confirmed by FACS analysis of cells derived from explanted aortas (p<0.05). Explanted aortas from Nox2-Tg had significantly higher levels of secreted pro-inflammatory cytokine, cyclophilin A (Cypa) at both baseline and after 5 days of in vivo AngII treatment compared to WT littermates. Compared to primary WT EC and VSMC, Nox2-Tg primary EC, but not primary VSMC, had increased ROS production which was accompanied by increased Cypa secretion and ERK1/2 activation. Furthermore, conditioned media from Nox2-Tg EC induced a greater ERK1/2 phosphorylation compared to the media of WT controls. In conclusion, we demonstrate for the first time that a specific increase in endothelial ROS through the over-expression of Nox2 is sufficient to induce aortic dissection in response to AngII stimulation. Endothelial secreted Cypa could be the signalling mechanism by which increased endothelial ROS regulates the inflammatory response and the susceptibility to aortic dissection.